A systemic approach to identifying sustainable community-based interventions for improving adolescent mental health: a participatory group model building and design protocol - Megan Keenan; Leanne Freeman; Ediane Santana de Lima; Katie Potter; Tim Hobbs; Ellis Ballard; Peter Fonagy (Health Research Policy and Systems)
Abstract Background The deteriorating mental health of children and young people in the United Kingdom poses a challenge that services and policy makers have found difficult to tackle. Kailo responds to this issue with a community-based participatory and systemically informed strategy, perceiving mental health and well-being as a dynamic state shaped by the interplay of broader health determinants. The initiative works to explore, define and implement locally relevant solutions to challenges shaping the mental health and well-being of young people. Kailo unfolds in three stages within each locale. These stages encompass: “early discovery”, “deeper discovery and co-design” and “implementation”. This document delves into the participatory group model building and design protocol occurring in the “deeper discovery and co-design” stage of the project. Methods Participatory methods, such as group model building, are effective in articulating and building consensus on complex issues like the social determinants of adolescent mental health. This paper describes the protocol for application of group model building within the Kailo design process to develop causal loop diagrams and pinpoint leverage points for improving adolescent mental health. It also suggests a method for considering modifications to delivery within a unique project context and in alignment with participants’ needs. This paper sets out to define the approach and clarify the objectives these engagements aim to fulfil. The method adapts existing group model building (GMB) protocols for use in a community setting. The engagements will involve groups of local young people and existing community members. To assess the success of the session’s implementation post-delivery, the study utilizes existing frameworks for fidelity evaluations, which define a core and flex model. Discussion The method described enables an integration of diverse local understandings of complex processes which provides a platform for creating co-designed interventions. This protocol can be used to further strengthen research and design through incorporating complexity and participation into the formulation of contextually relevant policies and practices. The strengths and limitations of the approach are discussed.